Terminology for Translators — an Implementation of ISO 12620 - Bononno, Robert (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2000)
AbstractAs far as translators are concerned, terminology is primarily an ad hoc affair, more a matter of filling in the blanks in their knowledge than systematically studying a constellation of terms in a given universe of discourse. This article sketches the historical background of terminology and discusses the importance of terminology management for translators. More specifically, it outlines a method by which translators can make use of the data categories discussed in ISO 12620 in their daily work. A specific implementation of these data categories, using off-the-shelf software, is presented.